First principles calculation of topological invariants of lossy photonic crystals - Prudêncio, R. F.; Silveirinha, M. G. (Nanophotonics and Micro/Nano Optics International Conference 2019, Book of Abstracts, 2019)
Topological systems have exciting properties that may lead to new physics. The Chern numbers of a material platform are usually written in terms of the Berry curvature which depends on the normal modes of the system. From a computational point of view the calculation of the Chern number can be a rather formidable problem. Here, we use a gauge invariant Green’s function method (Phys. Rev. B, 99, 125155, 2019) to determine the topological invariants. We apply the method to a lossy photonic crystal formed by a hexagonal array of ferrite cylinders embedded in air with radius r=0.35a [Fig.1a]. The Chern numbers are calculated from first principles, i.e., without a tight-binding approximation.